2021
DOI: 10.1177/1035719x21993938
|View full text |Cite
|
Sign up to set email alerts
|

Generalising from qualitative evaluation

Abstract: Evaluations are often focused on assessing merit, value, outcome or some other feature of a programme, project, policy or some other object. Evaluation research is then more concerned with the particular rather than the general – even more so, when qualitative methods are used. But does this mean that evaluations should not be used to generalise? If it is possible to generalise from evaluations, under what circumstances can this be legitimately achieved? The authors of this article have previously argued for g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…Similar studies can be conducted in other contexts and compare the findings. Hence, the findings from the study showed analytical generalisations rather than statistical generalisations (Guenther & Falk, 2021).…”
Section: Discussion Of Findingsmentioning
confidence: 83%
“…Similar studies can be conducted in other contexts and compare the findings. Hence, the findings from the study showed analytical generalisations rather than statistical generalisations (Guenther & Falk, 2021).…”
Section: Discussion Of Findingsmentioning
confidence: 83%
“…They propose that, against conventional notions of analysis as a linear application of method, "thinking with theory does not come at the end of anything but is emergent and immanent to that which is becoming" (p. 1232). In this way, thinking with theory is a process that informs an analytic endeavor from the beginning, shaping the ways in which the world is experienced, data are generated, and sense is made (Guenther & Falk, 2021). Jackson and Mazzei (2018) outline the value of drawing on concepts from theories of various kinds to pursue "eruptions", which are analytic moves that push thinking beyond taken-forgranted conceptualizations of the topic of a given study.…”
Section: Methodsmentioning
confidence: 99%
“…They propose that, against conventional notions of analysis as a linear application of method, “thinking with theory does not come at the end of anything but is emergent and immanent to that which is becoming” (p. 1232). In this way, thinking with theory is a process that informs an analytic endeavor from the beginning, shaping the ways in which the world is experienced, data are generated, and sense is made (Guenther & Falk, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…There is a related/parallel argument that suggests evaluation studies can result in generalisation (Guenther and Falk, 2021) through iterative processes of theory building and testing (Guenther and Falk, 2019). Mark (2011), in his discussion about generalisability, calls for more attention to be given to 'translational theories ' (p. 38), leading to prediction based on what he describes as 'principled discovery' (p. 40).…”
Section: Evaluation Use and Theory Buildingmentioning
confidence: 99%
“…The interest in qualitative evaluation arises from the authors' use of qualitative and mixed methodologies in research and evaluation. The work here builds on previous work published in relation to generalising from qualitative research (Falk and Guenther, 2021;Guenther and Falk, 2019) and evaluation (Guenther and Falk, 2021).…”
Section: Introductionmentioning
confidence: 96%